1996
DOI: 10.1007/bf01799432
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in glycogen storage disease type I

Abstract: Summary In an attempt to detect acid maltase deficiency in neutrophils from patients with type II glycogenosis, without interference from the ‘renal’ α‐glucosidase activity present in these cells, we have evaluated the contribution of the renal component in the total activity measured at pH 4.0 in extracts of human neutrophils. The renal contribution is about 13–25% and renal glucosidase appears to be closely related to the enzyme present on the epithelium of small intestine, which is known to be inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…1 Pulmonary hypertension and early-onset atherosclerosis have been reported. 2,3 Thus, GSD-Ia is a severe, multi system disorder that results in significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1 Pulmonary hypertension and early-onset atherosclerosis have been reported. 2,3 Thus, GSD-Ia is a severe, multi system disorder that results in significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…To date, nine GSD I patients with PAH have been reported. 49,50,[157][158][159][160][161][162][163] Of these, five had concomitant conditions that were also associated with the development of PAH, including three patients with portocaval shunts, one patient with an atrial septal defect, and one patient with hereditary hemorrhagic telangiectasia. 33,49,84,[157][158][159]161 It has been suggested that abnormal handling of serotonin might be one event in a multistep process leading to PAH in GSD I patients.…”
Section: Cardiovascular Aspectsmentioning
confidence: 99%
“…The median patient age at the time of echocardiogram was 24 years, with a range of None of the echocardiograms reviewed showed evidence of PAH. Of the 6 patients in our review described previously by Kishnani et al, 7 2 had been noted to have estimated systolic pulmonary artery pressures >20 mm Hg (TR jet velocity >2.2 m/s). However, on follow-up, none of the patients showed abnormalities or progression to PAH on echocardiogram.…”
Section: Resultsmentioning
confidence: 73%